Poster: We Are Well: Well-being superpower booklets - Geraldine Burke; Priscilla Pettengell; Chris Hanger (2023)
Poster: We Are Well: Our well-being superpowers (booklets ) are part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. Participants were asked to describe their well-being superpowers and to then create a logo to represent these superpowers. Participants across generations then shared their superpowers as a get-to-know-you activity. Poster text: Some of our superpowers are the same. Some are different. It’s magic, learning together. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Melanie Attard, Aislinn Lalor, Megan Adams, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr. Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara and local community Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, Darug, and Wiradjuri First Nations consultant, artist, and educator. Founder of Your Green Prescription, Kursty Colemane, Darug, and Wiradjuri First Nations knowledge holder, artist, and educator.